2010
DOI: 10.1002/chir.20843
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in asymmetric oxidative coupling of 2‐naphthol and its derivatives

Abstract: The enantiomeric atropoisomers of 1,1'-binaphthyl-2,2'-diol (BINOL) have become one of the most widely used chiral ligands and auxiliaries for asymmetric synthesis. This review provides an overview of enantioselective synthesis of optical active BINOLs by straightforward asymmetric oxidative coupling of identical 2-naphthol and its substituted derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(45 citation statements)
references
References 90 publications
(70 reference statements)
0
45
0
Order By: Relevance
“…In addition to producing the desired cross-coupled biphenolic product, 538 the reaction is also accompanied by products derived from oxidative dimerization, higher molecular weight polymers as well as compounds housing C-O coupling motifs. [539][540][541][542][543] Seminal work on the intermolecular anodic oxidative coupling of phenols demonstrated that corypalline (210) could be electrochemically oxidized to the corresponding dimer (211, Scheme 63). [544][545][546][547][548] However, attempts to carry out the related intramolecular C-C coupling on laudanosine (212) resulted in oxidative dearomatization of one of the phenolic moieties and furnished O-methylflavinantine (213, Scheme 64).…”
Section: Electrochemical Oxidative Cross-couplingsmentioning
confidence: 99%
“…In addition to producing the desired cross-coupled biphenolic product, 538 the reaction is also accompanied by products derived from oxidative dimerization, higher molecular weight polymers as well as compounds housing C-O coupling motifs. [539][540][541][542][543] Seminal work on the intermolecular anodic oxidative coupling of phenols demonstrated that corypalline (210) could be electrochemically oxidized to the corresponding dimer (211, Scheme 63). [544][545][546][547][548] However, attempts to carry out the related intramolecular C-C coupling on laudanosine (212) resulted in oxidative dearomatization of one of the phenolic moieties and furnished O-methylflavinantine (213, Scheme 64).…”
Section: Electrochemical Oxidative Cross-couplingsmentioning
confidence: 99%
“…[17][18][19] Enantiomerically pure binols can be prepared either by resolution of a racemic product [1] , or chirality can be induced already during the synthesis in order to directly prepare enantiomerically pure product. [18,[20][21][22] In addition, further asymmetry in binol compounds can be introduced by crosscoupling of different naphthol molecules, which leads to binols with different subunits. [23][24][25][26] Several scenarios have been proposed as the mechanism for the naphthol coupling.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional preparations of BINOL and its derivatives require stoichiometric amounts of oxidants, but also some catalytic processes were developed, usually with oxygen serving as the terminal oxidant . Enantiomerically pure binols can be prepared either by resolution of a racemic product, or chirality can be induced already during the synthesis in order to directly prepare enantiomerically pure product . In addition, further asymmetry in binol compounds can be introduced by cross‐coupling of different naphthol molecules, which leads to binols with different subunits …”
Section: Introductionmentioning
confidence: 99%
“…[1] In particular, the generation of axial chirality between benzene rings is an important topic because such chirality is found in many biologically active compounds [2] and chiral ligands. [3] Regarding catalytic and enantioselective syntheses,c ross-coupling [4] and oxidative self-coupling of 2-naphthol derivatives [5] have been the subject of much research. In these approaches,axial chirality is generated by CÀCb ond formation between aryl groups.Incontrast, anew strategy for the generation of axial chirality along with the formation of benzene ring(s) was achieved by transition metal catalyzed [2+ +2+ +2] cycloaddition in 2004 (Scheme 1a).…”
mentioning
confidence: 99%